2010
DOI: 10.1007/s10571-010-9537-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Paeoniflorin Against Glutamate-Induced Neurotoxicity in PC12 Cells via Antioxidant Mechanisms and Ca2+ Antagonism

Abstract: Preclinical and clinical investigations have shown hippocampal neuronal atrophy and destruction were observed in patients with depression, which could be ameliorated by the treatment with antidepressants. Therefore, neuroprotection has been proposed to be one of the acting mechanisms of antidepressant. Paeoniflorin, a monoterpene glycoside, has been reported to display antidepressant-like effects in animal models of behavioral despair. The present study aimed to examine the protective effect of paeoniflorin on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…The procedure for culturing PC12 cells has been described elsewhere (Mao et al 2009(Mao et al , 2010c(Mao et al , 2011c. The cells were seeded onto 96-well culture plate at 2 9 10 4 cells/well, unless otherwise specified.…”
Section: Drugs and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for culturing PC12 cells has been described elsewhere (Mao et al 2009(Mao et al , 2010c(Mao et al , 2011c. The cells were seeded onto 96-well culture plate at 2 9 10 4 cells/well, unless otherwise specified.…”
Section: Drugs and Reagentsmentioning
confidence: 99%
“…Reactive oxygen species (ROS) level was measured using the DCFH-DA method (Mao et al 2010c). DCFH-DA is a non-fluorescent compound, and it can be enzymatically converted to highly fluorescent compound, DCF, in the presence of ROS.…”
Section: Measurement Of Intracellular Ros Levelmentioning
confidence: 99%
“…Fourth, several cell-based studies suggested that paeoniflorin isolate exhibits neuroprotective effects [30][31][32][33] . However, paeoniflorin (5) was found to have poor brain penetration in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Several Chishao monoterpene glycosides, including paeoniflorin, albiflorin, oxypaeoniflorin, benzoylpaeoniflorin, and galloylpaeoniflorin, have been detected in XueBiJing injection [18] . Cell-and animal-based studies have shown that paeoniflorin and other monoterpene glycosides exhibit anti-inflammatory, antiplatelet, antithrombosis, antioxidative, and neuroprotective properties [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Due to these pharmacological properties, several bioanalytical assays were developed to measure plasma concentrations of paeoniflorin and albiflorin [34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…Paeoniflorin (PF), a monoterpene glycoside isolated from the aqueous extract of the Chinese herb Radix Paeoniae alba, was reported to exert wide pharmacological effects in the nervous system ( Fig. 1) [1,[10][11][12]21]. Previous studies have identified that PF could attenuate the neurotoxicity induced by β-amyloid in the animal model and…”
Section: Introductionmentioning
confidence: 99%